2009
DOI: 10.1021/ma900041c
|View full text |Cite
|
Sign up to set email alerts
|

Half-Titanocene-Based Catalysts in the Syndiospecific Polymerization of Styrenes: Possible Oxidation States of the Titanium Species and Geometries of the Active Sites

Abstract: Half-titanocenes (CpCH 2 CH 2 O)TiCl 2 (1) and (CpCH 2 CH 2 OCH 3 )TiCl 3 (2), (Cp ) cyclopentadienyl), activated by methylaluminoxane (MAO), have been tested in the polymerization of styrene, p-methylstyrene, and p-chlorostyrene. Both catalysts produce syndiotactic polystyrene and poly-p-methylstyrene in the whole range of explored temperatures and concentrations. In the polymerization of p-chlorostyrene, however, catalyst 1 affords a syndiotactic polymer only at the low temperature and the high monomer conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 44 publications
4
43
0
Order By: Relevance
“…[20][21][22][23][24][25][26] However, recent studies have indicated that a tetravalent titanium (Ti 4+ ) species is also generated and can similarly promote styrene polymerization in the CpTiCl 3 /MAO type catalyst system, independent of the Ti 3+ active species. [27][28][29][30][31] An analogous Ti 4+ species is believed to be the active species in olefin polymerization by metallocene-type catalyst systems (such as Cp 2 TiCl 2 /MAO). 32 Nomura and others 12,33 have reported that a half-titanocene catalyst, which has an aryloxy-type ligand, conducts the copolymerization of ethylene and styrene, resulting in effective synthesis of the random copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] However, recent studies have indicated that a tetravalent titanium (Ti 4+ ) species is also generated and can similarly promote styrene polymerization in the CpTiCl 3 /MAO type catalyst system, independent of the Ti 3+ active species. [27][28][29][30][31] An analogous Ti 4+ species is believed to be the active species in olefin polymerization by metallocene-type catalyst systems (such as Cp 2 TiCl 2 /MAO). 32 Nomura and others 12,33 have reported that a half-titanocene catalyst, which has an aryloxy-type ligand, conducts the copolymerization of ethylene and styrene, resulting in effective synthesis of the random copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…In polymerization of styrene, both catalysts 1 and 2 activated by MAO, produce syndiotactic polystyrene (sPS)9 while, according with previous work,10 in polymerization of 1,3‐butadiene, they prevailingly produce 1,4‐ cis polybutadiene.…”
Section: Resultsmentioning
confidence: 56%
“…It is worth noting that 1 based catalyst produces syndiotactic 1,2‐poly(4‐MPD) with a narrow molecular weight distribution. Evidently, as it takes place in the polymerization of styrene,9 one of the two obtained catalytic specie is able to polymerize 4‐MPD to stereoregular polymer, whereas the other one is ineffective in the polymerization of this monomer, probably because of different coordination of 4‐MPD in comparison with that of other conjugated diolefins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CpTiR 3 can be usable in combination with the borane or borate cocatalyst (225)(226)(227)(228)(229). Half-titanocene complexes with the phenolate group, such as 57, (230) and the CGC titanium complex 58 are also utilized for syndiotactic polymerization of styrene (231). Titanium complexes with two Cp ligands also promote syndiospecific styrene polymerization, but their activity is significantly lower than half-titanocene complexes (232).…”
Section: Polymerization Of Styrenementioning
confidence: 99%